PERBANDINGAN E-GOVERNMENT DI NEGARA INDONESIA DAN AUSTRALIA - Winda Agustin; Aminullah (As-Sulthan Journal of Education, 2026)
This study compares e-government implementation between Indonesia and Australia to identify factors influencing the success of digital transformation in both countries. Using a qualitative approach with a comparative study method, this study analyzes the differences and similarities between the two countries' e-government systems through the Technology-Organization-Environment (TOE) Framework. Data were collected through documentary studies of e-government policies, regulations, and evaluation reports, in-depth interviews with key stakeholders, and direct observation of government digital platforms such as SPBE Indonesia and myGov Australia. The results indicate that Australia has a more mature and integrated e-government system, with service penetration reaching 90% of the population, supported by a robust digital infrastructure, highly competent human resources, and a solid governance structure through the Digital Transformation Agency. In contrast, Indonesia still faces various challenges such as a digital infrastructure gap between urban and rural areas, fragmented systems that are not yet optimally integrated, weak coordination between agencies, and diverse digital literacy levels. Nevertheless, Indonesia has shown significant progress through innovative approaches such as the development of mobile-first applications and partnerships with the local private sector that are adaptive to local contexts and limitations. This study recommends that Indonesia gradually accelerate digital infrastructure development, increase the capacity of civil servants through ongoing training programs, strengthen governance structures with clearer authority, and adopt a user-centric design approach in developing government digital services. The research findings contribute to the e-government literature by demonstrating that contextual factors such as socio-economic conditions, geographic characteristics, and institutional capacity play a crucial role in determining e-government implementation strategies and outcomes. Therefore, best practices cannot be directly transferred without substantive adaptation to local contexts.